Study on follow up of patients in the Department of Radiotherapy in a teaching hospital - Hussain, Quazi Mushtaq; Mahbub-Ul-Alam, Md; Hai, MA (TAJ: Journal of Teachers Association, 2009)
Follow-up of patients is one of the most important parts of cancer management. But in our country as most of the patients do not come for follow-up, at present it is only possible to find the total number of patients, their sex, number of patients planned for radiotherapy and chemotherapy and or other treatment modality and their percentage but not possible to find out the cure rate and survival rate due to above mentioned limitations. So it is suggested to improve the documentation system in a computerized manner and increase patient counseling so that patients come for follow-up and when ever a patient comes whether he or she is new or old can be recognized at once. doi: 10.3329/taj.v19i2.3150 TAJ 2006; 19(2): 57-59